Benefits of Creatine Supplementation in Elderly Individuals (Research, Society and Development, 2022)
The aging process is characterized by simultaneous changes in the biopsychosocial spheres, which are responsible for the involvement of chronic non-communicable diseases and commonly lead to functional disability and imply in the individual's quality of life. Biological changes directly interfere with the aging process, and the musculoskeletal system is highlighted for being a predictor of autonomy because when in decline it favors functional disability and its serious consequences. Knowing that adequate nutrition is one of the mitigating factors of the disabilities of aging, a bibliographic review was carried out in order to analyze creatine as a therapeutic resource in pathologies associated with aging. Studies point to creatine supplementation as a well-tolerated and safe strategy in elderly individuals. Positive effects were evidenced in both gain in lean mass and muscle strength as well as possible neuroprotective effects.